The Effect of a Jigsaw Type Cooperative Learning Approach Towards Primary Students' Understanding Concepts of Science Learning in Primary Schools - Anggy Giri Prawiyogi; Yulistina Nur DS; Tia Latifatusadiah; Tarpan Suparman; Hesti Widiastuti (Postgraduate, University of Mataram, 2024)
This research is based on the results of observations and interviews at SD Al-Hikmah Indonesia that the learning carried out is still limited due to time so that only the target of material completion is pursued, while the achievement of learning outcomes and students' understanding of concepts is still lacking. Learning is only student-centered. For this reason, there is a need for appropriate and effective methods in learning. Therefore, researchers tried to use a jigsaw type cooperative learning approach to overcome this problem. This research uses a pretest-posttest control group design, data collection techniques using test and non-test data. Test data was obtained from pre-test and post-test results, while non-test data was obtained from questionnaires. This research took as subjects students of class IV A and students of class IV B. In this research three meetings were held which included pre-test, learning and post-test. After applying this approach, the average gain for the experimental class was 0.49 and the control class was 0.25. The results of the research show that there is an increase in students' post-test results in learning using the jigsaw type cooperative learning approach. So it can be concluded that there is an influence of this approach on science learning on the subject of natural resources. The results of this research are recommended as a reference for further research, especially research that uses a jigsaw type cooperative learning approach in learning natural resources in order to improve students' understanding of concepts better in the future.